Allergic Colitis in Infants Related to Cow’s Milk: Clinical Characteristics, Pathologic Changes, and Immunologic Findings - Man-Chun Yu; Chia-Lun Tsai; Yao-Jong Yang; Sing-San Yang; Li-Hui Wang; Chung-Ta Lee; Ren-Long Jan; Jiu-Yao Wang (Pediatrics and Neonatology)
Allergic colitis (AC) is an inflammatory condition characterized by eosinophils infiltrating the colonic wall. It can be a benign and/or severe illness among gastrointestinal diseases in infants. Methods: We report five infants who, since January 2009, in whom AC under fibrotic endoscopic examinations has been diagnosed. The criterion for histopathologic diagnosis of AC in this study was five or more eosinophils per high-power field. Patients’ clinical symptoms, pathologic findings, and immunologic studies, such as specific antibodies against component of cow’s milk protein, were compared with those of allergic children without AC and those of nonatopic control children. Results: Histopathologic examinations of biopsy specimens revealed acute inflammation with characteristic eosinophilic infiltration of lamina propria (5–15 eosinophils per high-power field) in all five patients. They all had strongly positive skin prick tests against milk protein, which were not correlated with in vitro allergen-specific immunoglobulin (Ig) E levels. In contrast, there were significantly higher levels of IgE antibodies, and lower specific IgG4 and IgA levels to components and whole milk proteins in AC, as compared to control children without AC. Conclusion: Endoscopic biopsy specimens of intestine confirm the diagnosis of AC. However, allergen skin prick test and IgE antibody to milk protein components also provide helpful diagnostic tools for this rare disease in children.